On the Variability in Preterm Birth Rate, Birth Weight, and Somatic Classification among Neonates of Mothers with the Same Body Mass Index - Krentz, H.; Voigt, M.; Guthmann, F.; Hesse, V.; Straube, S. (Zeitschrift für Geburtshilfe und Neonatologie, 2011)
Maternal height and weight are important determinants of perinatal outcomes. Height and weight can be combined in the measure of body mass index (BMI). We aimed to investigate the utility of maternal BMI as a predictor of perinatal outcomes.Based on data collected between 1995 and 2000 as part of the German perinatal survey, we examined singleton pregnancies of women with BMIs of 18, 24, or 30. We compared preterm birth rate, birth weight, and the somatic classification of neonates as small, appropriate, or large for gestational age (SGA, AGA, LGA) for women with heights of 150 cm and 180 cm for each BMI.For women with a BMI of 18 (24; 30) and a height of 150 cm, the preterm birth rate was 13.9% (9.1%; 12.5%); for women with the same BMI and a height of 180 cm the preterm birth rate was 12.1% (6.1%; 4.4%). Birth weight for women with a BMI of 18 (24; 30) and a height of 150 cm was 2 889 g (3 170 g; 3 147 g); for women with the same BMI and a height of 180 cm it was 3 314 g (3 629 g; 3 753 g). The LGA rate for women with a BMI of 18 (24; 30) and a height of 150 cm was 2.1% (5.2%; 5.2%); for women with the same BMI and a height of 180 cm it was 7.7% (20.5%; 27.7%).There is considerable variability in perinatal outcomes between women with the same BMI but different heights. This limits the utility of BMI as a predictor of perinatal outcomes.
Keywords: maternal BMI; preterm birth rate; birth weight; somatic classification of neonates